Waste nutrient solutions from full-scale open hydroponic cultivation: Dynamics of effluent quality and removal of nitrogen and phosphorus using a pilot-scale sequencing batch reactor. (1st March 2021) - Kwon, Man Jae; Hwang, Yunho; Lee, Juyeon; Ham, Baknoon; Rahman, Arifur; Azam, Hossain; Yang, Jung-Seok
Abstract: Hydroponic cultivation is revolutionizing agricultural crop production techniques all over the world owing to its minimal environmental footprint, enhanced pest control, and high crop yield. However, waste nutrient solutions (WNS) generated from hydroponic systems contain high concentrations of N and P; moreover, they are discharged into surface and subsurface environments, leading to eutrophication and subsequent ecosystem degradation. In this study, the nutrient concentrations in WNS from 10 hydroponic indoor tomato, capsicum, and strawberry farms (greenhouses) were monitored for up to six months. The concentrations of N and P in WNS discharged from these farms were 48.0–494.0 mg L −1 and 12.7–96.9 mg L −1, respectively, which exceeded the Korean water quality guidelines (40.0 mg L −1 N and 4.0 mg L −1 P) for effluents. These concentrations were varied and dependent on the supplied nutrient concentrations, crop types, and growth stages. In general, the concentrations of N and P were in the following order: tomato > capsicum > strawberry. High N as NO3 − and P as PO4 3− but low organic C in WNS warrant subsequent treatment before discharge. Therefore, this study tested a pilot-scale sequencing batch reactor (SBR) system as a potential technology for WNS treatment. The SBR system had BOD, COD, nitrate, and phosphate removal efficiency of 100, 100, 89.5, and 99.8%, respectively. In addition, the SBR system removed other cations such as Ca 2+, dissolved Fe, K +, Mg 2+, and Na + and the removal efficiencies of those ions were 48, 67, 18, 14 and 15%, respectively. Lower methanol addition (0.63 mg L −1 ) and extended aeration ( 30 min) improved SBR performance efficiency of C, N, and P removal. Thus, SBR showed significant promise as a treatment alternative to WNS pollutants originating from hydroponic systems. Graphical abstract: Image 1 Highlights: N and P concentrations in WNS were higher in tomato and capsicum farms than in strawberry farms. The rate and extent of N and P removal in WNS were investigated using a biological sequencing batch reactor. The daily removal rates of N and P were up to 100% with the amendment of methanol.